Student-Based Disaster Management: Alternative Solutions to Build a Disaster-Resilient City - Dina Pramesti Regita; Bambang Syaeful Hadi (Journal of Governance, 2022)
Abstract: Disasters that have occurred in the past should serve as a valuable lesson for those who will come after them. This is the most important factor in determining how prepared a community is. According to common knowledge the city of Palu is one of the cities that is particularly vulnerable to natural disasters due to its geographical location, which is situated between the confluence of two tectonic plates of the Pacific Ocean and Asia, necessitating the need for residents who live in the area to be prepared for such events. As a result, the purpose of this study is to determine the value of studying disaster preparedness from a young age in order to reduce the impact of disasters generated through the use of a spatial education strategy. The descriptive method is used with a qualitative approach in this investigation. The findings indicate that preparedness education should begin at a young age in order to instill a sense of vigilance in kids, rather than a sense of terror. Education in geography, and specifically geography-based disaster preparedness learning materials, is critical to establishing a solid foundation in disaster preparedness learning from a physical and geographical perspective.Keywords: Learning, Preparedness, Geography Education, Students, Disaster.